The Influence of Financial Literacy, Financial Inclusion, and Ease of Use of the QRIS System on the Business Continuity of Culinary MSMEs in Pontianak City - Khairunnisa, Hanna; Safitri, Heni; Hariyanto, Dedi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the influence of Financial Literacy, Financial Inclusion, and Ease of Use of the QRIS System on the Business Continuity of MSMEs in the culinary sector in Pontianak City. Employing a quantitative approach with an associative method and involving 150 respondents selected through purposive sampling, data were collected via questionnaires and analyzed using multiple linear regression with the assistance of SPSS. The findings indicate that, simultaneously, the three independent variables have a significant effect on business continuity. Partially, Financial Literacy and Ease of Use of QRIS show significant effects on business continuity, while Financial Inclusion does not demonstrate a significant impact. The coefficient of determination (R²) is 0.385, suggesting that 38.5% of the variation in business continuity can be explained by the three variables. These results underscore the importance of enhancing financial literacy and utilizing accessible technology to support the sustainability of MSMEs. Therefore, it is recommended that MSME actors strengthen their financial literacy and maximize the use of QRIS in daily operations. Meanwhile, the government and supporting institutions are encouraged to expand access to digital financial literacy training and to develop a more inclusive financial system. For future research, it is advisable to include additional variables such as service quality or business innovation and to consider mixed-method approaches and broader geographic coverage to obtain more comprehensive insights.